2021
DOI: 10.3390/toxics9050096
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake and Toxicological Effects of Differently Sized Zinc Oxide Nanoparticles in Intestinal Cells

Abstract: Due to their beneficial properties, the use of zinc oxide nanoparticles (ZnO NP) is constantly increasing, especially in consumer-related areas, such as food packaging and food additives, which is leading to an increased oral uptake of ZnO NP. Consequently, the aim of our study was to investigate the cellular uptake of two differently sized ZnO NP (<50 nm and <100 nm; 12–1229 µmol/L) using two human intestinal cell lines (Caco-2 and LT97) and to examine the possible resulting toxic effects. ZnO NP (<5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 66 publications
2
13
0
2
Order By: Relevance
“…The smaller nanoparticles (e.g., ZnO_Intra; about 16.7 nm) have an extraordinary ability to internalize into living cells through different biological mechanisms and reach the nucleus, thereby generating genotoxic damage with the consequent triggering of apoptosis. Mittag et al [74] investigated the cellular uptake of two differently sized ZnO NPs (<50 nm and <100 nm) against two human intestinal cell lines (Caco-2 and LT97). The outcomes of this study showed that ZnO NPs, at smaller sizes (<50 nm), led to the formation of micronuclei in LT97 cells.…”
Section: Cytotoxicity Of Zno Npsmentioning
confidence: 99%
“…The smaller nanoparticles (e.g., ZnO_Intra; about 16.7 nm) have an extraordinary ability to internalize into living cells through different biological mechanisms and reach the nucleus, thereby generating genotoxic damage with the consequent triggering of apoptosis. Mittag et al [74] investigated the cellular uptake of two differently sized ZnO NPs (<50 nm and <100 nm) against two human intestinal cell lines (Caco-2 and LT97). The outcomes of this study showed that ZnO NPs, at smaller sizes (<50 nm), led to the formation of micronuclei in LT97 cells.…”
Section: Cytotoxicity Of Zno Npsmentioning
confidence: 99%
“…There were only minor differences between ZnO NP and ZnCl 2 regarding the proportions of free zinc ions and bonded zinc. Digested ZnO NP showed no structural similarities with the pristine large, rod-shaped particles, which we have already characterized [ 28 ].…”
Section: Discussionmentioning
confidence: 91%
“…It was speculated, however, that pony-sized ZnO NPs were more toxic than large particles, merely at low concentrations, whereas they may present an equal level of risk at high concentrations, possibly due to the tendency of pony-sized nanomaterials to agglomerate [ 56 ]. In addition to cell viability indicators, the teratogenic potential was also mainly reflected in the ZnO NPs with a small diameter, which could lead to the emergence of a micronucleus in the LT97 cell at 50 nm, not at 100 nm [ 57 ]. As is consistent with these comparative tests, here, the RNA sequencing clarified that compared with ordinary ZnO, ZnO NPs demonstrated stronger lethality to hepatocytes, brought more severe inhibition of cell detoxification and caused more interference with antioxidation processes and membrane function ( Figure 4 , Figure 5 and Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%